2005
DOI: 10.1534/genetics.104.035717
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Experimental Evolution in Escherichia coli. XII. DNA Topology as a Key Target of Selection

Abstract: The genetic bases of adaptation are being investigated in 12 populations of Escherichia coli, founded from a common ancestor and serially propagated for 20,000 generations, during which time they achieved substantial fitness gains. Each day, populations alternated between active growth and nutrient exhaustion. DNA supercoiling in bacteria is influenced by nutritional state, and DNA topology helps coordinate the overall pattern of gene expression in response to environmental changes. We therefore examined wheth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
153
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 131 publications
(158 citation statements)
references
References 55 publications
5
153
0
Order By: Relevance
“…This is because of the cells ability to more rapidly metabolize lactate, the sole electron donor and carbon source provided. Previous laboratory evolution studies have identified mutations in regulatory elements (Cooper et al, 2003;Crozat et al, 2005;Herring et al, 2006;Knight et al, 2006;D'Argenio et al, 2007;Giraud et al, 2008 et al, 2010), but these were all within global regulatory 'hubs' that subsequently affected gene expression on a large scale. In contrast, this study offers the finding of a mutated transcriptional regulator that appears to have a very narrow gene target, repression of two genes that encode for a single key enzyme.…”
Section: Discussionmentioning
confidence: 99%
“…This is because of the cells ability to more rapidly metabolize lactate, the sole electron donor and carbon source provided. Previous laboratory evolution studies have identified mutations in regulatory elements (Cooper et al, 2003;Crozat et al, 2005;Herring et al, 2006;Knight et al, 2006;D'Argenio et al, 2007;Giraud et al, 2008 et al, 2010), but these were all within global regulatory 'hubs' that subsequently affected gene expression on a large scale. In contrast, this study offers the finding of a mutated transcriptional regulator that appears to have a very narrow gene target, repression of two genes that encode for a single key enzyme.…”
Section: Discussionmentioning
confidence: 99%
“…Ten populations evolved increased DNA supercoiling (27), and those populations examined to date show parallel changes in global gene-expression profiles (4,28,29). At least three genes have substitutions in all 12 populations (30,31), and several others have substitutions in many populations (27)(28)(29)(30), even though most loci harbor no substitutions in any of them (32). At the same time, there has also been some divergence between populations.…”
mentioning
confidence: 99%
“…All evolved higher maximum growth rates on glucose, shorter lag phases upon transfer into fresh medium, reduced peak population densities, and larger average cell sizes relative to their ancestor (22)(23)(24)(25)(26). Ten populations evolved increased DNA supercoiling (27), and those populations examined to date show parallel changes in global gene-expression profiles (4,28,29). At least three genes have substitutions in all 12 populations (30,31), and several others have substitutions in many populations (27)(28)(29)(30), even though most loci harbor no substitutions in any of them (32).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The traits generated are generally genetic and quantitative, increase directionally throughout the period of selection, and involve both regulatory and structural adaptations (Castle 1951;Paquin and Adams 1983a,b;Cohan and Hoffmann 1986;Lenski and Travisano 1994;Ferea et al 1999;De Visser and Lenski 2002;Dunham et al 2002;Buckling et al 2003;Cooper et al 2003;Elena and Lenski 2003;Riehle et al 2003;Zeyl et al 2003Zeyl et al , 2005Laurie et al 2004;Crozat et al 2005;Grimberg and Zeyl 2005;Rifkin et al 2005;De Visser and Rozen 2006;Pelosi et al 2006). These studies, however, can be intensive in both labor and resources.…”
Section: Discussionmentioning
confidence: 99%